2017
DOI: 10.3390/atmos8010012
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Temperature Fluctuation in Urban Areas of Pakistan

Abstract: Annual temperature data from thirty meteorological stations in Pakistan's major urban areas were selected to investigate trends in annual average and maximum temperature during . A combination of parametric and non-parametric tests including linear regression, the Mann-Kendall trend test and Sen's slope estimator was used for the analysis. Annual average and maximum temperature series showed an overall increasing trend for 90% of the stations and a decreasing trend for 10% of the stations in the study area. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
(110 reference statements)
0
3
0
Order By: Relevance
“…To detect abrupt changes or shifts in the temporal trend of precipitation indices, we used the non-parametric sequential Mann-Kendall (SqMK) test. Moreover, linear regression and two tailed Student's t-test were used to detect the significant linear trends in the precipitation indices over the study region [75,76]. The selected statistical techniques have been widely used by various researchers in their climatological and hydrological studies over different climatic regions of the world [18,52,[77][78][79][80][81].…”
Section: Statistical Techniquesmentioning
confidence: 99%
“…To detect abrupt changes or shifts in the temporal trend of precipitation indices, we used the non-parametric sequential Mann-Kendall (SqMK) test. Moreover, linear regression and two tailed Student's t-test were used to detect the significant linear trends in the precipitation indices over the study region [75,76]. The selected statistical techniques have been widely used by various researchers in their climatological and hydrological studies over different climatic regions of the world [18,52,[77][78][79][80][81].…”
Section: Statistical Techniquesmentioning
confidence: 99%
“…Numerous climatic studies have suggested an actual increase in temperature(Anjum et al 2017), by about 0.24 °C per decade between 1960 and 2007 (M. A Khan et al 2016)…”
mentioning
confidence: 99%
“…Mann‐Kendall (MK) trend test is used for trend detection in hydrometeorological records such as temperature, rainfall, evaporation, evapotranspiration, streamflow, and water quality . In addition, Şen_ITA is used by many researchers, which gives successful results to identify trend component in a given time series such as temperature, precipitation, water quality and relative humidity, solar radiation, streamflow, water level, evapotranspiration in the literature.…”
Section: Introductionmentioning
confidence: 99%